Popularitas Tari Piring sebagai Identitas Budaya Minangkabau - -, Indrayuda (PANGGUNG, 2013)
ABSTRACTÃÂ This article aims to explain the existence of Tari Piring dance as a culture identity of Minang- kabau people, both the people who live in the origin area and outside the area. Tari Piring dance is a traditional cultural heritage of Minangkabau people which is used and preserved by Minangkabau people in their life so that it becomes culture identity of Minangkabau people. As the identity of Minangkabau people, Piring dance is able to express attitudes and behaviors as well as the charac- teristics of Minangkabau people. The dance can serve as a reflection of social and cultural life style of Minangkabau society. Through Tari Piring performance, the outsider can understand Minangkabau people and their culture. Tari Piring, therefore, is getting more adhere to the social life of Minang- kabau people in West Sumatra and in the regions overseas. In the spirit of togetherness, Minang- kabau society preserves the existence of Piring dance as the identity and cultural heritage up to the present time.ÃÂ Keywords: Piring Dance, Minangkabau cultureÃÂ ÃÂ ABSTRAKÃÂ Artikel ini bertujuan untuk menjelaskan keberadaan Tari Piring sebagai identitas bu- daya masyarakat Minangkabau, baik yang berada di daerah asal maupun di daerah peran- tauan. Tari Piring merupakan warisan budaya tradisional masyarakat Minangkabau yang digunakan dan dilestarikan oleh masyarakat Minangkabau dalam kehidupannya sehingga menjadi identitas budaya Minangkabau. Sebagai jati diri masyarakat Minangkabau, Tari Piring mampu mengungkapkan sikap dan prilaku serta karakteristik orang Minangkabau. Tari Piring dapat berperan sebagai cerminan dari corak kehidupan sosial budaya masyara- kat Minangkabau. Melalui pertunjukan Tari Piring, masyarakat luar dapat memahami orang Minangkabau dan budayanya. Oleh karena itu, sampai saat ini Tari Piring semakin melekat dengan kehidupan sosial masyarakat Minangkabau di Sumatera Barat maupun di daerah perantauan. Dengan semangat kebersamaan, masyarakat Minangkabau mampu mempertahankan keberadaan Tari Piring sebagai identitas dan warisan budayanya hingga masa kini.ÃÂ Kata kunci : Tari Piring, budaya Minangkabau